Recent advances and prospects of fiber-shaped rechargeable aqueous alkaline batteries - Yang, Jiao (2022)
The prosperity in portable and wearable electronics has stimulated researchers to develop safe, environmentally friendly, and efficient energy-storage technologies. Increased efforts have recently been made to fabricate high-performance rechargeable aqueous alkaline batteries (RAABs) as the frontrunner to complement and even replace the dominant lithium-ion batteries for large-scale energy storage due to the limited lithium resources and the use of flammable and toxic organic electrolyte. Compared with the conventional planar RAABs, fiber-shaped RAABs (FRAABs) manifest several intriguing features, such as miniaturization, adaptability, and weavability, making them an attractive candidate to power wearable and portable electronics. Herein, an overview of the recent progress in FRAABs by categories of fiber-shaped aqueous rechargeable Zn-based batteries, Fe−Ni batteries, and Bi−Ni batteries, with respect to the active electrode materials, device configurations, and battery properties, is comprehensively presented. Finally, the remaining challenges and possible solutions are emphasized as a useful guide for the further development of FRAABs.